Efektifitas Peran Bintara Pembina Desa (Babinsa) dalam Menjaga Keamanan dan Ketertiban di Kelurahan Babakan - Evangelista, Beverly (TSAQOFAH, 2021)
The issue of security and order in an area is very important, therefore, the role of babinsa in maintaining security and order in the Babakan Village area is very important to study. From this background, it is necessary to formulate a problem, namely how effective is the role of Babinsa in maintaining security and order in the Babakan Village area. The study used a qualitative approach. From the results of the research, the authors show that the effectiveness of the Babinsa's role in maintaining security and order in the Babakan Village area is based on the Regulation of the Army Chief of Staff Number 19/IV/2008 dated April 8, 2008 by implementing several tasks, namely: anjangsana to all houses in the area. assisted villages so that Babinsa is known to the public, participates in all activities in the community, helps communities affected by disasters, participates in religious and regional arts activities, actively participates in siskampling activities with the community, teaches UN to students, residents and village youth groups and teaches people to evacuate if there is a disaster and determine the place of refuge.